PEMEROLEHAN FONOLOGIS PADA ANAK USIA 0—2 TAHUN - R. Hery Budhiono (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This research focuses on the acquisition of phonology. The aims of this resaerch are to provide a description of phonemes that have been acquired and its order and to give a brief description about subject’s language acquisition and development. The subject of this writing is a girl named Azmirainy Azizah who is also the writer’s first daughter. The form of the data, mostly, are utterances and dialogues and are taken with a camera-phone and also note-taking techniques. All data, then, are verified and paraphrased in its smaller form. According to the findings, the subject follows some universal rules in acquiring sounds: the contrast between bilabial and alveolar is first acquired, followed by the contrast between bilabial and velar sounds. The order in acquiring sounds is bilabials, alveolars, palatals, velars, fricatives, and laterals. The central-low vowel /a/ is acquired first and followed by the other vowels, i.e. /i/, /ε/, /u/, /ɔ/, /o/, /e/, and /ə/